(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Fatmawati M, Suwanti LT, Mufasirin, Hambarruk W, Sukesi LE, Rofiah, Novianto E, Wahyuningtyas BK. 2022. A comparative study among dairy goat breeds in Lumajang and Malang, East Java based on milk organoleptic and milk composition. Biodiversitas 23: 2899-2903. The Regencies of Lumajang and Malang have the potential for local dairy goats to support food security and food safety. In Lumajang and Malang there are a diversity of dairy goats that breed Senduro, Crossbreed Etawa, Sapera, and Menggolo. This study aimed to compare the milk quality of various breeds of dairy goats in Lumajang and Malang regencies based on organoleptic and composition tests. The total sample was 161 milk samples from Lumajang (115 dairy goats) and Malang (56 dairy goats). The organoleptic test of milk was carried out by testing the freshness, smell, taste, viscosity, and color of the milk. The milk composition test used lactoscan. The analysis consisted of the Chi-Square test for organoleptic and the Kruskal Wallis for milk composition test. The results show that the quality of goat’s milk is of premium quality. The order of milk quality based on fat content is milk from Menggolo, Senduro, Etawa, and Sapera breeds. This study concluded that the breed of dairy goat influence the composition and quality of goat’s milk. The milk quality of all dairy goat breeds from Lumajang and Malang was premium quality, but the Menggolo goat is the best, so it can be developed to increase local food productivity.